Visualization of Concurrent Epicardial and Microvascular Coronary Artery Disease in a Patient with Systemic Lupus Erythematosus by Magnetic Resonance Imaging. Issue 1 (February 2022) - McGill, Liam; Gill, Callum; Schoepf, U. Joseph; Bayer, Richard R.; Suranyi, Pal; Varga-Szemes, Akos
Abstract : Abstract: We present a patient with history of systemic lupus erythematosus who presented with acute chest pain. Electrocardiography, invasive coronary angiography, and cardiac MRI were performed during the course of her evaluation. Invasive coronary angiography demonstrated obstructive disease in the diagonal system and cardiovascular MRI confirmed an anterior infarct consistent with the electrocardiographic findings. However, MRI also revealed focal inferoseptal hypoperfusion inconsistent with electrocardiographic and angiographic findings. Rather, these findings indicate the presence of concurrent microvascular coronary artery disease, which has a high prevalence among women with autoimmune disease.